MODIFIKASI CAMPURAN PERKERASAN AC-WC DENGAN ASPAL BUTON & SERAT RAMI - Wildan Alifian S.P; Kurnia Hadi Putra; Ratih Sekartadji; Theresia mca4 (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to determine the effect of adding ramie rope powder on the Marshall characteristics of Asphalt Concrete-Wearing Course (AC-WC) mixtures using a combination of Buton asphalt and penetration grade 60/70 asphalt. The study was conducted using variations of ramie rope powder content of 0%, 1%, and 2%. The research methods included asphalt and aggregate material testing, AC-WC mix design, specimen preparation, and Marshall testing consisting of stability, flow, VIM, VMA, VFB, and Marshall Quotient (MQ). The results showed that the addition of ramie rope powder affected the Marshall characteristics of the asphalt mixture. The stability value changed in each variation of the mixture, while the flow value tended to increase as the ramie rope powder content increased. The use of ramie rope powder in AC-WC mixtures is expected to be an environmentally friendly alternative additive material that can improve pavement performance